Glial Cells in the Genesis and Regulation of Circadian Rhythms - Chi-Castañeda, Donají; Ortega, Arturo (Frontiers in Physiology, 2018)
Circadian rhythms are biological oscillations with a period of 24 h. These rhythms are orchestrated by a circadian timekeeper in the suprachiasmatic nucleus of the hypothalamus, the circadian “master clock,” which exactly adjusts clock outputs to solar time via photic synchronization. At the molecular level, circadian rhythms are generated by the interaction of positive and negative feedback loops of transcriptional and translational processes of the so-called “clock genes.” A large number of clock genes encode numerous proteins that regulate their own transcription and that of other genes, collectively known as “clock-controlled genes.” In addition to the sleep/wake cycle, many cellular processes are regulated by circadian rhythms, including synaptic plasticity in which an exquisite interplay between neurons and glial cells takes place. In particular, there is compelling evidence suggesting that glial cells participate in and regulate synaptic plasticity in a circadian fashion, possibly representing the missing cellular and physiological link between circadian rhythms with learning and cognition processes. Here we review recent studies in support of this hypothesis, focusing on the interplay between glial cells, synaptic plasticity, and circadian rhythmogenesis.